PENGARUH METODE EKSPERIMEN TELUR TERHADAP KEMAMPUAN SAINS ANAK DI TAMAN KANAK-KANAK NEGERI PEMBINA 01 SUTERA - Aulia Abidza; Nurhafizah; Yaswinda; Nur Hazizah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Importance of fostering scientific ability in young children through engaging and tangible learning experiences inspired this study. Simple experiments, like those employing eggs as a medium, can be a useful tool. Finding out how the egg experiment affected the scientific knowledge of kindergarteners at Taman Kanak-kanak Negeri Pembina 01 Sutera was the driving force for this study. Acquiring and applying scientific information, methods, and perspectives are all part of these scientific abilities. It was a quantitative research that employed a quasi-experimental design. The sample was drawn from two classes, B1 and B2, each with eleven children, and the population was comprised of all pupils at Taman Kanak-kanak Perguruan Islam. Interviews, documentation, and organized observation were the methods used to gather data. Utilizing SPSS 25.0 for Windows, the data underwent analysis through hypothesis testing (t-test), normality tests, and homogeneity tests. The results demonstrated that compared to the control class, the experimental group, who utilized the egg experiment method, exhibited superior scientific competency. The control group's average gain score was 11.09 whereas the experimental group's was 12.90. A statistically significant difference was shown by the significance value (2-tailed), which was 0.02 < 0.05. It follows that the egg experiment is an effective tool for fostering scientific literacy in young children.